A new scenario for ‹c› vacancy loop formation in zirconium based on atomic-scale modeling. (15th October 2019) - Christiaen, B.; Domain, C.; Thuinet, L.; Ambard, A.; Legris, A.
Abstract: The growth of zirconium alloys under irradiation is a phenomenon experimentally identified and associated with the development beyond a threshold dose of dislocation loops with vacancy character having a Burgers vector with a component parallel to the c axis. In this work, by combining atomic simulations (DFT and empirical potential) and continuous modeling, we show that prismatic stacking fault pyramids or bipyramids whose base rests on the basal plane of the hcp structure are likely precursors to the formation of ‹c› vacancy loops. In other words, these would not be formed by progressive accretion of vacancies but rather by collapse of the pyramids or bipyramids beyond a certain size. This mechanism could explain the fact that the ‹c› vacancy loops are never observed below a size of the order of 10 nm and their appearance at high fluence. Graphical abstract: Image 1